Surviving Rape: Profile and Coping Reactions of Filipino Rape Survivors Seen at the UP-PGH Women's Desk from January 1999 to December 2000 - Lopez, June Pagaduan; Chua, Aimee G.; de Guzman, Ma. Rossana (Review of Women's Studies, 2005)
This paper, a hospital-based review of sexual assault cases from 1999 to 2000, is a descriptive study of rape victims who asked for the assistance of UP-PGH Women's Desk. It focuses on the medical and behavioral aspects including the person's coping reactions before, during and after the incident. It provides a profile of the 114 survivors, legal and medical definition of terms and other data important in the understanding of rape and assault cases.